Effect of foot reflexology on perimenopausal mild hypertension - Nermeen Kareem Eid Bleedy; Hala Mohamed Hanafy Omara; Hossam Eldien Hussien; Mohamed Ahmed Mohamed Awad (Cairo : Nermeen Kareem Eid Bleedy, 2021)
This study was conducted to study the effect of foot reflexology on perimenopausal mild hypertension. Fifty perimenopausal women suffering from mild hypertension were selected randomly from the outpatient clinic of the gynecology department in Sayed Galal Hospital in Cairo, Al Azhar University. Their ages were ranged from 48 to 50 years old. Their body mass index (BMI) did not exceed 30kg/m2. The physician diagnosed them as mild hypertensive patients (stage 1). Patients with bronchial asthma, history of hypertension before the 4th decade, diabetes mellitus and mental health problems such as depression and anxiety are excluded from the study. The design of the study was an experimental study (two groups pre-test post-test design). The patients were divided randomly into two groups equal in number (A&B): Group A (Control group); consisted of twenty-five patients. They performed aerobic exercises only three times per week for 8 weeks. Group B (Study group); consisted of twenty-five patients.They performed aerobic exercises and received foot reflexology three times per week for 8 weeks. Body mass index was assessed using a standard weight and height scale. Blood pressure was assessed using a mercury sphygmomanometer, blood analysis for TC, TG, LDL and HDL for both groups A and B before and after treatment. Results showed that; within groups, there was significant decrease in systolic blood pressure, diastolic blood pressure, cholesterol, triglyceride, LDL and significant increase in HDL in both groups A and B post treatment in comparison with pre treatment values
Thesis (Ph.D.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Gynecology and Obstetrics
Issued also as CD
Keywords: Foot Reflexology; Hypertension; Perimenopausal